Ataluren metabolism: Ataluren-O-1β-acyl glucuronide is a stable circulating metabolite in mouse, rat, dog and human. (June 2021) - Ma, Jiyuan; Risher, Nicole; Northcutt, Valerie; Moon, Young-Choon; Weetall, Marla; Welch, Ellen; Colacino, Joseph; Almstead, Neil; Kong, Ronald
Abstract: Ataluren is an aromatic acid derivative with a 1, 2, 4-oxodiazole moiety. Ataluren- O -1β-acyl glucuronide is a prominent circulatory metabolite in mice, rats, dogs, and humans following oral administration of ataluren. The objective of this paper was to evaluate the stability in vitro and in vivo of ataluren- O -1β-acyl glucuronide metabolite. Ultrahigh performance liquid chromatography-mass spectrometry methods were developed to separate and monitor ataluren- O -1β-acyl glucuronide and its possible migration isomers. In vitro stability was assessed in phosphate buffered saline as well as in control rat and human plasma. The disappearance of ataluren- O -1β-acyl glucuronide and the formation of migration isomers were monitored by the ultrahigh performance liquid chromatography-mass spectrometry methods. In vitro, ataluren- O -1β-acyl glucuronide underwent isomerization with an estimated half-life of approximately 1 h. However, ataluren- O -1β-acyl glucuronide was stable and was the only detectable acyl glucuronide following oral administration of ataluren in mice, rats, dogs, and humans using the same analytical methods. Ataluren acyl glucuronide in mouse, rat, dog, and human plasma could be hydrolyzed by β-glucuronidase, further confirming the structure of O -1β-acyl glucuronide. These results demonstrated that ataluren- O -1β-acyl glucuronide did not undergo migration in vivo. No clinical safety concern related to ataluren- O -1β-acyl glucuronide migration has been detected.